ITER-relevant 600 s steady-state extraction of negative hydrogen ions at the test facility ELISE - D. Wünderlich; R. Riedl; M. Fröschle; A. Heiler; A. Navarro; D. Yordanov; A. Döring; U. Fantz (Nuclear Fusion)
The neutral beam heating system for the future international fusion experiment ITER will be based on radio-frequency driven ion sources delivering a large (≈1 × 2 m ^2 ) and homogeneous negative hydrogen or deuterium ion beam of several ten Amperes for several hundred seconds. The size scaling experiment ELISE (Extraction from a Large Ion Source Experiment) is an integral part of the R&D road-map towards the ITER neutral beam heating system. Recently, 90% of the ITER target for the extracted current density was achieved in hydrogen for 600 s, increasing the pulse length over which such current densities can be achieved by a factor of more than ten. For ten second beam pulses the ITER target current density was achieved. These breakthrough results are made possible by using a steady-state capable high-voltage power supply together with an improved version of internal potential rods and a modified topology of the magnetic filter field.